MEMPERKUAT TANGGA DRAMATIK FILM “SENANG BERTEMU DENGANMU” MELALUI PENERAPAN EDITING ASPEK RITMIK - I Gusti Ngurah Agung Jaya Pangestu Suastika; Nyoman Lia Susanthi; Gede Basuyoga Prabhawita (CALACCITRA: JURNAL FILM DAN TELEVISI, 2021)
The fictional film entitled “Senang Bertemu Denganmu” describe the inner conflict of a young man after getting to know someone without an encounter. The young man also got several answers to questions that he had not known throughout his life. The inner conflict is illustrated by the graphic of Hudson's story. There are 6 acts in the graphic so the editor must be able to adjust the rhythm in each scene to strengthen the dramatic ladder of the film. The formulation of the problem that arises is how to apply the rhythmic aspect of editing to strengthen the dramatic ladder of the film